Precipitation Variability Affects Aboveground Biomass Directly and Indirectly via Plant Functional Traits in the Desert Steppe of Inner Mongolia, Northern China - Cheng, Huan; Gong, Yuanbo; Zuo, Xiaoan (Frontiers in Plant Science, 2021)
Clarifying the response of community and dominance species to climate change is crucial for disentangling the mechanism of the ecosystem evolution and predicting the prospective dynamics of communities under the global climate scenario. We examined how precipitation changes affect community structure and aboveground biomass according to manipulated precipitation experiments in the desert steppe of Inner Mongolia, China. Bayesian model and structural equation models (SEM) were used to test variation and causal relationship among precipitation, plant diversity, functional attributes, and aboveground biomass (AGB). The results showed that the responses of species richness, evenness, and plant community weighted means traits to precipitation changes in amount and year were significant. The structural equation models demonstrated that precipitation change in amount and year have a direct effect on richness, evenness, and CWM for height, leaf area (LA), specific leaf area (SLA), leaf dry matter content (DLMC), leaf nitrogen content (LNC) and leaf carbon content (LCC) and AGB; thereinto CWM for height and LDMC had direct positive effect on AGB; LA had direct negative effect on AGB. Three dominant species showed diverse adaptation and resource utilization strategies in response to precipitation changes. A. polyrhizum showed an increase in height under the precipitation treatments that promoted AGB, whereas the AGB of P. harmala and S. glareosa was boosted through alterations in height and LA. Our results highlight the asynchronism of variation in community composition and structure, leaf functional traits in precipitation-AGB relationship. We proposed that altered AGB resulted from the direct and indirect effects of plant functional traits (plant height, LA, LDMC) not species diversity, those are likely candidate traits given they are mechanistically linked to precipitation changes and affected aboveground biomass in desert-steppe.